READIBUDDY: A Culturally Relevant Literacy Tool for Empowering Malaysian Girls - Raman, Kumutha; M Xavier, Jane Xavierine; Khairuddin, Nur Izzati; Hashim, Harwati; Arulraj David, Solomon; Rhoel C. Cruz, Geoffrey (Forum for Linguistic Studies, 2025)
Literacy development remains a critical challenge among young learners in rural Malaysia, particularly for girls who face sociocultural barriers, limited exposure, and a lack of relatable reading materials. Existing English language tools are often generic and fail to align with the linguistic needs and cultural realities of underserved communities. As a result, girls in Orang Asli and remote regions experience lower reading motivation and higher dropout rates. This study examined whether a culturally grounded, scaffolded digital literacy platform could improve English reading proficiency, motivation, and identity affirmation among rural Malaysian girls. To address this aim, the ReadiBuddy platform was developed and piloted over six weeks of classroom and home-based learning. ReadiBuddy features localized stories across three genres (Fantasy, Science, History), scaffolded by CEFR levels (A1–B2), bilingual toggling, pronunciation playback, comprehension quizzes, and a gamified interface. Teachers supported the implementation using a real-time dashboard and differentiated instruction tools. Findings revealed significant improvements in reading proficiency, learner engagement, and cultural connection. Students responded positively to the use of Malaysian female heroes and culturally familiar narratives, while teachers viewed the platform as a practical supplement for under-resourced classrooms. The results also reflect key principles in second language acquisition, including scaffolded comprehensible input, code-switching strategies, and the role of learner identity in literacy development. ReadiBuddy contributes to SDG 4 (Quality Education), SDG 5 (Gender Equality), and SDG 10 (Reduced Inequality). It exemplifies a socially responsive and pedagogically sound innovation that bridges literacy gaps through engaging, inclusive, and contextually relevant digital learning, thus empowering a generation of confident, literate girls.